Lingkungan Sosial dan Perilaku Konsumsi Moke Pada Remaja di Kelurahan Madawat - Rochaelin Theresia Liseuz Seno Nanga; Stefanus H. Gusti Ma; Damianus Tola (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
This study aims to determine the effect of the social environment on alcohol consumption behavior (moke) in adolescent boys in the Madawat Village. This study uses quantitative methods with questionnaire data collection techniques (questionnaires) and documentation where the questionnaires are distributed to male adolescent respondents aged 11-22 years and documented in the form of photos in the field. From the results of the study, it is known that the social environment has a significant influence on the consumption behavior of moke in adolescents, especially boys. These results state that the social environment is one of the factors that can influence a person and even a group to be able to take an action as well as changes from each individual. Where the constant value for the regression equation is 12,366 with positive parameters. This regression coefficient can be explained that if there is an increase in the Social Environment variable (X) by one unit, it will result in an increase in the Alcohol Consumption Behavior (Moke) variable (Y) by 654 units. From the results of research using the t-test obtained 6.743 > 1.994, so Ho is rejected, meaning that the Social Environment (X) has a significant effect on Moke Consumption Behavior (Y)